Tinjauan Yurdis Pencemaran Lingkungan Limbah Pabrik Tahu di Kabupaten Jombang : (Studi Kasus Pabrik Tahu, Desa Sumbermulyo, Kecamatan Jogoroto, Kabupaten Jombang) - Muhammad Juang Tribuana (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the issue of environmental pollution caused by tofu factory waste in Jombang Regency, particularly in Sumbermulyo Village, Jogoroto District. The focus of the study is directed at analyzing regulations as well as obstacles in law enforcement related to tofu industrial waste pollution. The method used is a normative juridical approach with the main legal foundation being Law Number 32 of 2009 concerning Environmental Protection and Management, and Jombang Regency Regional Regulation Number 8 of 2017. The results show that although comprehensive legal instruments are available, the implementation and enforcement of the law remain suboptimal. The main obstacles lie in the low public awareness, limited supervision, and weak sanctions imposed. These conditions have led to ongoing environmental pollution, threatening public health and ecosystem sustainability. Therefore, strengthening regulations, optimizing supervision, and increasing the active role of the government, law enforcement agencies, and community participation are urgently needed to preserve the environment.